2019
DOI: 10.1186/s12889-019-7535-1
|View full text |Cite
|
Sign up to set email alerts
|

The density of electronic gambling machines and area-level socioeconomic status in Finland: a country with a legal monopoly on gambling and a decentralised system of EGMs

Abstract: Background Electronic gambling machines (EGMs) are considered a risky form of gambling. Internationally, studies have reported that the density of EGMs tends to be higher in socioeconomically disadvantaged areas than in more advantaged ones. We examined whether this holds true in the Finnish context where a decentralised system of EGMs guarantees wide accessibility to this form of gambling. More precisely, we investigated the association between the density of EGMs and area-level socio-economic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
(30 reference statements)
2
23
0
Order By: Relevance
“…Access to electronic gambling machines (EGMs) and video lottery terminals (VLTs) outside casinos is associated with participation and problem gambling in cross‐sectional studies [62, 63]. However, such correlations may also result from other factors; for instance, the machines are often concentrated in economically deprived neighbourhoods [64, 65]. Studies on access restricted by governments suggest that limitations must be substantial to have effects.…”
Section: Effects Of Regulating Availability and Pricementioning
confidence: 99%
“…Access to electronic gambling machines (EGMs) and video lottery terminals (VLTs) outside casinos is associated with participation and problem gambling in cross‐sectional studies [62, 63]. However, such correlations may also result from other factors; for instance, the machines are often concentrated in economically deprived neighbourhoods [64, 65]. Studies on access restricted by governments suggest that limitations must be substantial to have effects.…”
Section: Effects Of Regulating Availability and Pricementioning
confidence: 99%
“…Elgar´s study [ 14 ] suggested that youth who live in economically unequal settings and perceive a lack of social support are at higher risk of disordered gambling. The relationship between gambling and SES might be also explained by the higher density of electronic gambling machines in areas with lower SES [ 15 ]. Based on a longitudinal study, Auger et al [ 16 ] showed that individuals with lower SES and impulsivity had earlier age of gambling onset.…”
Section: Introductionmentioning
confidence: 99%
“…While the effect sizes of the sunshine-and sports-based prediction errors observed in the present study are rather subtle compared to these SES effects, the generality of the prediction error effects (particularly with respect to sunshine) across geographies is noteworthy. Moving forward, it would be beneficial to investigate the number of retailers within each FSA and its relation to lottery purchases, as previous studies have found that the density of electronic gambling machines was negatively correlated with SES (Raisamo et al, 2019). Relatedly, online lottery ticket purchasing was introduced by OLG at the beginning of 2015 (midway through the period we analyzed), but our dataset only covers in-person lottery ticket purchases.…”
Section: Discussionmentioning
confidence: 99%